Active learning using learning management system to improve students' competence in argumentative writing - Wardani Dwi Wihastyanang; Daning Hentasmaka; Rosi Anjarwati (Institut Agama Islam Negeri (IAIN) Palangka Raya, Indonesia, 2014)
Nowadays the educational paradigm has changed from passive learning into active learning where learners are actively involved in teaching and learning process. Internet, as one of the information and communication products, is believed to be able to facilitate an active and interactive teaching and learning process. One of the examples is the use of Learning Management System (LMS). LMS is viewed appropriate to be applied in teaching English especially the writing skill in which learners need more time and more exercises to improve their skills. The limited time of classroom meeting makes the need impossible to be fulfilled. By using LMS, the teaching and learning process can not only depend on the classroom meeting but also can be done outside the classroom anytime and anywhere. In this quasi-experimental research the researchers were eager to know the effectiveness of active learning by using LMS to improve students’ writing skill, especially in argumentative writing. The data was analyzed with ANCOVA using SPSS version 20. The result shows that the value of F-value is 5.505 and the significant value is .021 which is less than .05, and the F-value is higher than F-table (3.94). It means that the alternative hypothesis (Ha) is accepted. Thus, it can be concluded that teaching writing by using LMS is more effective than conventional classroom meeting.